STUDENTS’ MOTIVATION TOWARDS SCIENCE LEARNING (SMTSL) OF STEM STUDENTS OF UNIVERSITY OF BATANGAS, LIPA CITY - Albalate, Andre R; Larcia, Harris Daniel; Jaen, Josh Angelo; Pangan, Kevin Ryan; Garing, Alphie G (PEOPLE: International Journal of Social Sciences, 2018)
The main purpose of the study is to identify the levels of motivation of STEM (Science, Technology, Engineering, and Mathematics) students in University of Batangas, Lipa City (UBLC). It is necessary as motivation serves as a foundation for better understanding of concepts in an academic setting. The respondents are 111 grade 11 students who are enrolled during the Academic Year 2016-2017. The researchers assess the levels of motivation of students across four (4) sections of STEM strand. The research utilized a questionnaire SMTSL (Students Motivation Towards Science Learning), a survey questionnaire developed by Tuan, Chin, & Shieh (2005) which is composed of questions which is divided into six (6) domains of motivation namely, self-efficacy, active learning strategies, science learning value, performance goal, achievement goal and learning environment stimulation. Results showed that achievement goal ranked first (1st) among the six (6) domains. This suggests that students have satisfaction in every time they increase their competence in attaining achievements during science class. On the other hand, the data recognizes the performance goal as the least factor. However, the data shows that students do not agree nor disagree whether their goals towards science learning are to compete with other or simply get attention from the teacher. Based on these findings, it is recommended that UBLC considers factors of motivation in implementing science curriculum. This research will not only help students in understanding their motivation but will also help the institution to promote a better environment for learning. Additionally, the study will serve as a foundation for future researches related in assessment of motivation of students towards learning.